PELATIHAN PENINGKATAN KREATIVITAS GURU DALAM PERANCANGAN POSTER DAN PEMBELAJARAN FLIPPEDCLASSROOM DI IGABA SIDOARJO - Rindaningsih, Ida; Awaliyah, Warda; Rocmah, Luluk Iffatur; Stutik, Ika Ratna Indra (LPPM Universitas Bina Bangsa, 2024)
The Aisyiyah Bustanul Athfal Teachers Association (IGABA) is a community of Early Childhood Education (PAUD) teachers, one of which is in Sidoarjo. In this digital era, educators must master learning methods and technology in education. However, there are quite a few early childhood teachers who still have little knowledge regarding learning methods and educational technology, so the ABDIMAS team program is an effort to overcome the problems faced by IGABA Sidoarjo to provide training to increase creativity in designing posters and flipped classroom learning. The purpose of this activity is to provide assistance to IGABA teachers so that they can develop learning methods and technology in the digital era. The program implementation method is observation, idea planning, activity process, assistance and activity evaluation. This activity was carried out on August 21, 2024 at SMA Muhammadiyah 2 Sidoarjo with a mentoring process from August 22, 2024 to August 27, 2024. The results of this activity are posters that have been made and the application of flipped classroom learning that has began to be implemented by IGABA Sidoarjo.